2014
DOI: 10.1007/s10879-014-9288-6
|View full text |Cite
|
Sign up to set email alerts
|

Positive Motivational Interviewing: Activating Clients’ Strengths and Intrinsic Motivation to Change

Abstract: Motivational interviewing (MI) is a widely disseminated, scientifically-tested method of psychotherapy, which combines a supportive, collaborative and empathic counselling style with a consciously directive method as a means to positively resolve tension created by unresolved ambivalence about change. This article outlines MI as a positive approach to psychotherapy and considers some of its core concepts: the client-centered attitudes and its links with positive psychology interventions (PPIs). The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…During such therapeutic conversations, emphasis could be placed on the process rather than the outcome of their goal-directed endeavors to eliminate worries and pessimism. Also, it is possible that a therapist could appeal to somebody low in NFC using some sort of motivational interviewing strategy (Csillik, 2014). In line with recent treatments that focus on increasing CURIOSITY AND MENTAL HEALTH 18 positive emotion (Geschwind, Peeters, Drukker, van Os, & Wichers, 2011;Kim & Franklin, 2015), a lack of interest in learning and general curiosity about the world likely is contributing to a lack of joy in the person's life.…”
Section: Discussionmentioning
confidence: 99%
“…During such therapeutic conversations, emphasis could be placed on the process rather than the outcome of their goal-directed endeavors to eliminate worries and pessimism. Also, it is possible that a therapist could appeal to somebody low in NFC using some sort of motivational interviewing strategy (Csillik, 2014). In line with recent treatments that focus on increasing CURIOSITY AND MENTAL HEALTH 18 positive emotion (Geschwind, Peeters, Drukker, van Os, & Wichers, 2011;Kim & Franklin, 2015), a lack of interest in learning and general curiosity about the world likely is contributing to a lack of joy in the person's life.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have found MI promoted treatment engagement, retention, and adherence with large effect sizes (Hettema, Steele, & Miller, 2005). Similar effect sizes have been reported when MI is added to other active psychotherapieseach enhancing the impact of the other (Csillik, 2015). As such, it is possible that MI would maintain the athletes' engagement with the MAC program and adoption of behaviour patterns learned during MAC.…”
Section: Introductionmentioning
confidence: 64%
“…Further, it is the first intervention to combine the MAC protocol within an MI framework, thereby providing an increased specificity for how the program was delivered. Although we cannot ascertain which aspects of the program (MAC, MI or both) contributed to the outcomes, it has been suggested that combining MI with other interventions can help to increase adherence, promote synergistic effects, and lead to better outcomes (Csillik, 2015;Nar-King, Earnshaw, & Breckon, 2013). It is possible that the MI framework served to increase intrinsic motivation for change (Csillik, 2015), and complemented the value-and strength-driven behaviour component of the MAC program.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…At the very beginning, MI could be used to activate clients’ strengths and intrinsic motivation, their level of readiness to change and thus adherence to treatment. Therefore, MI can be employed during a PPI to increase motivation when encountering resistance to change (Csillik, 2015) as it has been shown to facilitate participation in treatment, improve hope and empowerment, and increase purpose in life in individuals with DD (Glossman et al , 2013). In addition, as CBT approaches are widely used within PSIs, positive CBT may be another beneficial approach (Bannink, 2013).…”
Section: Discussionmentioning
confidence: 99%